Analisa DFA Terhadap Rancangan Body Mesin Pencacah Plastik Kemasan 220ml Portable - Agung Perdana Putra; Subkhan Subkhan; Yang Fitri Arriyani (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Complex problems in machine assembly processes are often caused by inefficient product designs, such as excessive component count and long assembly time. This study aims to analyze the application of the Design for Assembly (DFA) method to the design of a plastic shredder machine body to improve assembly efficiency and manufacturing ease. The research method includes component analysis, assembly feasibility evaluation using DFA parameters, and assembly efficiency index calculation based on the Boothroyd and Dewhurst approach. The analysis results show that the redesigned body using DFA reduced the number of components by 25% and decreased estimated assembly time by 32% compared to the initial design. Moreover, the assembly efficiency increased from 45% to 66%, indicating a simpler, more ergonomic, and cost-effective design. Thus, the DFA method proved effective in optimizing the design of the plastic shredder machine body, making it easier to assemble and manufacture without reducing its structural strength.